ANALISIS SISTEM AKUTANSI PENGGAJIAN PADA UD. RAHMAT JAYA ABADI DI KEL. INDUHA, KEC. LATAMBAGA, KAB. KOLAKA - Indar. B, Windi Ratu; Turi, La Ode; Chairunnas, Arnadi (Komunitas Manajemen Kompetitif, 2026)
This study aims to (1) analyze the payroll system and procedures implemented at UD. Rahmat Jaya. The analysis process is carried out through the stages of reading, reviewing, and understanding the data by following the analysis model of Miles and Huberman (2010). The payroll accounting system at UD. Rahmat Jaya Abadi is structured based on monthly salary payments made every 31st. The procedure has five main pillars in the operation of this system, namely the personnel function and time recording managed by the secretary, and three other functions, preparation of payroll, accounting, and finance, all of which are the responsibility of the treasurer. The documentation implemented in the payroll process consists of four main types of documents, namely salary change documents, payroll lists, payroll recaps, and payroll envelopes. Of the eight documents that should be implemented in the payroll system, only four of them are used routinely. This condition indicates a weakness in the internal control system, especially in the supervision of the employee attendance recording process which is still carried out manually by the secretary. This manual recording creates the potential for errors and data manipulation, and causes the information processing process to be less efficient. Furthermore, there is no clear separation of duties between accounting and finance functions, as both are carried out by the same treasurer. This has the potential to impact the accuracy, integrity, and transparency of payroll data.